Diabetes Melitus (DM) Sebagai Implementasi Pengabdian Masyarakat Berbasis Edukasi Di RW RT 002 / 002 Kelurahan Jayaloka Kecamatan Tebing Tinggi Kabupaten Empat Lawang - Yanti, Fitri; Fadhilah, Athia Azka; Saputri, Septi Suci Aulia; Putri , Riski Erviana; Situmorang, Ronalen Br.; Rohani, Tuti; Azissah, Danur (Jurnal Kewirausahaan dan Bisnis, 2020)
Diabetes mellitus or what people generally call diabetes is a chronic disease that can be suffered throughout life. Diabetes has 2 types, namely type 1 diabetes mellitus which is the result of an autoimmune reaction to pancreatic islet cell proteins, then type 2 diabetes which is caused by a combination of genetic factors related to impaired insulin secretion, insulin resistance and environmental factors such as obesity, overeating, undereating, exercise and stress, and aging. The purpose of this Thematic KKN activity is to increase public knowledge about Diabetes Mellitus through activities of community service based on health education for participants who experience Diabetes Mellitus. The methods used include Counseling about Diabetes Mellitus using leaflet media, TTV and Blood Sugar Examination, Demonstration of making herbal medicine to lower blood sugar levels, namely cinnamon decoction and Educating for periodic health checks at health centers. The results of the activity showed that out of 57 people studied, 7 out of 19 people with diabetes mellitus were male and 13 out of 38 people with diabetes mellitus were female. This means that more women experience DM in RT 002/RW 002, Jayaloka sub-district, Empat Lawang district in 2025. The results obtained are that counseling has been carried out well, the community already knows what diabetes mellitus is, but ongoing education is needed by the health center so that the community always remembers what diabetes is along with its signs and symptoms. Follow-up plan Hold counseling/education every month at every integrated health post. It is expected that the local government, especially the head of RT.002/RW 002, to invite the community to participate in health check-ups and adolescent/elderly integrated health posts carried out by the health center and the Tebing Tinggi health center to be more active in providing education to the community through health cadres about non-communicable diseases.